2019
DOI: 10.20473/joints.v7i2.2018.106-113
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Acl Injury With Posterior Tibial Slope, Intercondylar Notch Width Ratio, Age, and Sex

Abstract: Posterior tibial slope (PTS) has been proposed as a potential risk factor for ACL injury; however, studies that examined this relationship have provided inconclusive and sometimes contradictory results. Further characterization of this relationship may enable the medical community to identify individuals at greater risk for ACL injury and possibly characterize an anatomic target during surgical reconstruction. Medical records of 20 patients who underwent MRI of the knee and athroscopy procedure between August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…This finding is consistent with a study from Han et al, Andrade et al, Zeh et al, Shen et al, Volkan et al, Huang et al, Bayer et al, Priono et al study, where they reported a significant correlation between an increase in MTPS value with ACL tear incidence. 2,[9][10][11]13,15,18,26 They also found that the case group had a mean MTPS value of more than 14.4 degrees. 8 Between total and partial tear groups, it was found that NW, NWI, Q-angle and MTPS values were smaller in total tear group than in partial tear group.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This finding is consistent with a study from Han et al, Andrade et al, Zeh et al, Shen et al, Volkan et al, Huang et al, Bayer et al, Priono et al study, where they reported a significant correlation between an increase in MTPS value with ACL tear incidence. 2,[9][10][11]13,15,18,26 They also found that the case group had a mean MTPS value of more than 14.4 degrees. 8 Between total and partial tear groups, it was found that NW, NWI, Q-angle and MTPS values were smaller in total tear group than in partial tear group.…”
Section: Discussionmentioning
confidence: 89%
“…Anterior Cruciate Ligament (ACL) tear is one of the most common knee ligament abnormalities found in athletes, its incidence ranges from 29-38 per 100,000 people. [1][2][3] As a result, in the short term it might cause instability and in the long term it might cause degenerative process of knee joint. The most common type of ACL injury mechanism is non-contact type, due to pivoting movement, when the knee is slightly flexed and in valgus position then the femur undergoes external rotation as in foot maneuver movement during ball dribbling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selama cutting, atlet wanita menunjukan penurunan sudut fleksi hip, sudut knee valgus lebih besar daripada dengan pria. Hal ini menunjukan bahwa wanita lebih beresiko cedera ACL dibandingkan pria (Priono et al, 2018).…”
Section: Pendahuluanunclassified
“…Karakteristik berdasarkan gender pada penelitian ini juga menunjukan tidak ada perbedaan yang signifikan knee valgus mempengahruhi risk of injury responden. Hal ini berlawanan dengan hasil penelitian sebelumnya bahwa wanita lebih beresiko terkena knee injury dibandingkan laki-laki dilihat dari biomekanika anggota gerak bawah ketika melakukan cutting manuver (Priono et al, 2018). IMT berdasarkan hasil yang didapat dalam penelitian ini menunjukan tidak terdapat pengaruh yang signifikan juga.…”
Section: Hasilunclassified